TRANSFORMATIONAL LEADERSHIP STRATEGY EFFORTS TO IMPROVE THE QUALITY OF EDUCATION - Zahra, Evi Fatus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Currently, leadership is being implemented in institutions, especially in increasing professionalism in leadership in school institutions. Quality of education is the hope for educational institutions in facing tight life changes in several sectors, especially in the field of education, for a better future. In order to create quality education, it is necessary to play a leadership role in educational institutions. The role of leaders in educational institutions. This strategy includes developing an inspiring vision, effective communication, setting a good example, and providing ongoing support. The object of this research is SMPN2 Mlanding and the results of the research show that: transformative leadership is able to create. With this strategy, educational leaders are able to create an environment where innovation is encouraged , new ideas are supported, and cooperation is strengthened. This research method uses qualitative research with observation, interview , data collection techniques. The results of this research show that : 1 ) an inspirational vision, namely a leader must have a clear vision about the future of education. 2) active child involvement, namely a transformational leader involving all parties, especially students, teachers, parents and school staff. 3) with the strategy above, as a leader you must make changes and provide good strategies for the institutions you manage.